Relationship Between Leadership Styles And Emotional Intelligence Level Among Medical Educationists In Medical Institutions of Punjab - Mahmood, Asma; Sadiq, Naushaba (Pakistan Armed Forces Medical Journal, 2025)
Objective: To explore the relationship of leadership styles with the emotional intelligence level of medical educationists working in medical institutes of Punjab. Study Design: Cross-sectional study. Place and Duration of the Study: Medical colleges and universities in Punjab, Pakistan, from May 2024 to Sep 2024. Methodology: A cross-sectional study was carried out through universal sampling involving 30 medical educationists in leadership roles across various medical institutions in Punjab. The Genos Emotional Intelligence Inventory (Concise), with 31 items, and the Multifactor Leadership Questionnaire by Avolio and Bass, with 45 items, were used to determine the relationship of their leadership style with their emotional intelligence level. Results: The analysis yielded a significant positive correlation between emotional intelligence and transformational leadership (r=0.887) with p-value of <0.001, suggesting that elevated levels of emotional intelligence are associated with a greater prevalence of transformational leadership behaviors. Conversely, a negative correlation was identified between emotional intelligence and transactional leadership (r=-0.702), indicating that higher emotional intelligence correlates with a diminished reliance on transactional leadership styles. No significant correlation was established between emotional intelligence and laissez-faire leadership (r=-0.281). Conclusion: The study highlights the importance of emotional intelligence in effective leadership within medical education, recommending tailored development programs to cultivate this skill among educationists. Strengthening emotional intelligence could foster supportive learning environments and enhance outcomes for students and faculty alike.